If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4y + -3) + -3 = 3 Reorder the terms: 2(-3 + 4y) + -3 = 3 (-3 * 2 + 4y * 2) + -3 = 3 (-6 + 8y) + -3 = 3 Reorder the terms: -6 + -3 + 8y = 3 Combine like terms: -6 + -3 = -9 -9 + 8y = 3 Solving -9 + 8y = 3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 8y = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 8y = 3 + 9 8y = 3 + 9 Combine like terms: 3 + 9 = 12 8y = 12 Divide each side by '8'. y = 1.5 Simplifying y = 1.5
| 0.2(x+50)-6=0.4(3x+29) | | 5c-7+3=10 | | 2(r+5)=14 | | y=7sin(3(x+4))+2 | | -17=-2n-13-8n | | -4x-33=42-9x | | (14x-1)+(8x-7)=78 | | 20t+.15=30t+.10 | | 6y+12+2y=5y-2 | | 61=2x+17+x+17 | | 2n=10.06 | | 70=7x | | (2x-5)=-6 | | 9.5=v+2.8 | | 8x-6=3x+24 | | (2x-5)=6 | | 15x-8x=49 | | 12*c=108 | | 7y+8=-2y | | 2v+28=16+-4(v+7) | | -2(g+8)=64 | | -2-m=7 | | 4x^2=3x^2+9 | | 5(f-4)=-10 | | -5+5x=35 | | (x-2)=-2x-1 | | 8g-32=4g+16 | | X+17+4x=-29-4x-35 | | 1halfr+6=3-2r | | -10(s+3)=-71 | | (5x^3-6x^2+2x)+(-4x^2+3x)=42 | | 35x^2+76x+32= |